Compact and Wide-band Hybrid Metal-Insulator Plasmonic Directional Coupler - Talafi Noghani, Mahmoud; Vadjed Samiei, Mohammad Hashem (Photonics Letters of Poland, 2014)
A compact and wideband plasmonic directional coupler is proposed based on the hybrid metal-insulator slab waveguide (HMISW). Transfer matrix method (TMM) is adopted to analyze the multilayer structure. The hybrid waveguide is composed of a metallic layer of silver and two dielectric layers of silica (SiO2) and silicon (Si) with high index contrast. Coupling length and maximum transferred power are optimized according to dielectric layer thicknesses. It is shown that sub-micron coupling length is achieved with wide bandwidth and high efficiency, being advantageous to conventional directional couplers Full Text: PDF References P. Berini, "Plasmon-polariton waves guided by thin lossy metal films of finite width: Bound modes of symmetric structures", Phys. Rev. B, 61, 10484-10503 (2000). CrossRef R. Zia, M.D. Selker, and M.L. Brongersma, "Leaky and bound modes of surface plasmon waveguides", Phys. Rev. B, 71, 165431 (2005). CrossRef R. Zia, M.D. Selker, P.B. Catrysse, and M.I. Brongersma, "Geometries and materials for subwavelength surface plasmon modes", J. Opt. Soc. Am. A, 21, 2442-2446 (2004). CrossRef G. Veronis, and S. Fan, "Guided subwavelength plasmonic mode supported by a slot in a thin metal film", Opt. Lett., 30, 3359?3361 (2005). CrossRef A. V. Krasavin and A. V. Zayats, "Passive photonic elements based on dielectric-loaded surface plasmon polariton waveguides", Appl. Phys. Lett., 90, 211101 (2007). CrossRef R. F. Oulton, V. J. Sorger, D. A. Genov, D. F. P. Pile, and X. Zhang, "A hybrid plasmonic waveguide for subwavelength confinement and long-range propagation", Nature Photonics, 2, 496-500 (2008). CrossRef M. Z. F. Alam, J. S. Aitchison and M. Mojahedi, "Theoretical Analysis of Hybrid Plasmonic Waveguide", IEEE J. of Selec. Topics in Quant. Elec., 19, 4602008 (2013). CrossRef M. T. Noghani and M. H. V. Samiei, "Analysis and Optimum Design of Hybrid Plasmonic Slab Waveguides", Springer Plasmonics, 8, 1155-1168 (2013). CrossRef A. Boltasseva, T. Nikolajsen, K. Leosson, K. Kjaer, M. S. Larsen, and S. I. Bozhevolnyi, "Integrated optical components utilizing long-range surface plasmon polaritons", IEEE J. of Lightwave Tech., 23, 413?422 (2005). CrossRef Y. Wang, R. Islam, and G. V. Eleftheriades, "An ultra-short contra-directional coupler utilizing surface plasmon-polaritons at optical frequencies", Opt. Exp., 14, 413?422 (2006). CrossRef H. Zhao, X. G. Guang, and J. Huang, "Novel optical directional coupler based on surface plasmon polaritons", Physica E: Low-dim. Systems and Nanostruct., 40, 3025?3029 (2008). CrossRef P. Dastmalchi, N. Granpayeh, and M. Rasouli Disfani, "Investigation of coupling length in a semi-cylindrical surface plasmonic coupler", Springer Appl. Phys. A, 103, 741?744 (2011). CrossRef M. Z. Alam, J. S. Aitchison, and M. Mojahedi, "Polarization-independent hybrid plasmonic coupler for a silicon on insulator platform", Opt. Lett., 37, 3417?3419 (2012). CrossRef P.B. Johnson and R.W. Christy, "Optical Constants of the Noble Metals", Physical Review B, 6, 4370-4379 (1972). CrossRef